2017
DOI: 10.1186/s12933-016-0486-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of statin use and hypertriglyceridemia with diabetic macular edema in patients with type 2 diabetes and diabetic retinopathy

Abstract: BackgroundTo investigate the effects of dyslipidemia and statin therapy on progression of diabetic retinopathy and diabetic macular edema in patients with type 2 diabetes.MethodsThe medical records of 110 patients with type 2 diabetes (70 statin users and 40 non-users) were retrospectively reviewed. The two outcome measures were progression of diabetic retinopathy by two or more steps on the early treatment diabetic retinopathy study scale and diabetic macular edema based on optical coherence tomography. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 53 publications
6
57
1
1
Order By: Relevance
“…Still, simvastatin has been shown to delay the progression of DR in patients with hypercholesterolaemia, 20 and atorvastatin has been shown to decrease hard exudates of the retina and subfoveal migration of the lipids in the fovea, both associated with diabetic macular oedema. 23 Our findings suggest that an association between use of statins and incident DR, any treatment for DR and DME were consistent for statin use. 23 Our findings suggest that an association between use of statins and incident DR, any treatment for DR and DME were consistent for statin use.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Still, simvastatin has been shown to delay the progression of DR in patients with hypercholesterolaemia, 20 and atorvastatin has been shown to decrease hard exudates of the retina and subfoveal migration of the lipids in the fovea, both associated with diabetic macular oedema. 23 Our findings suggest that an association between use of statins and incident DR, any treatment for DR and DME were consistent for statin use. 23 Our findings suggest that an association between use of statins and incident DR, any treatment for DR and DME were consistent for statin use.…”
Section: Discussionsupporting
confidence: 63%
“…21 The Steno-2 study, in which statin was used in 85% of patients, involved an intensive multifactorial intervention including management of glycaemia, blood pressure and lipid concentration along with lifestyle modification which was associated with a reduction in the risk of microvascular complications including DR. 22 In one study, the risk of DME was also reduced, with a significant reduction in OR of 0.33 (95% CI, 0.12-0.91; P = .032) by statin use in 110 patients with type 2 diabetes mellitus. 23 Our findings suggest that an association between use of statins and incident DR, any treatment for DR and DME were consistent for statin use. Interestingly, point estimates for use of fibrates suggest that they might provide more benefit compared to statins, perhaps explained by the number of patients using fibrates compared to those using statins.…”
Section: Discussionsupporting
confidence: 63%
“…As is known, patients with T2D usually have dyslipidemia, an important risk factor for macroangiopathies such as PAD and CVD, which are manifested by atherosclerosis [46][47][48]. Although there is still no exact definition underlying the association between atherosclerosis and DR, some studies have suggested that the pathogenesis of these 2 conditions may have risk factors in common [49].…”
Section: Discussionmentioning
confidence: 99%
“…While statin use is associated with improvement in such retinal exudates, systemically it is also associated with a lower degree of myocardial microangiopathy and systolic dysfunction in patients with dilated cardiomyopathy (137). Use of the PPARantagonist, fenofibrate, has been demonstrated to reduce the risk of progression of non-proliferative diabetic retinopathy by up to 40%, but whether this is related to the lipid lowering or other effects is unclear (138,139).…”
Section: Lipid Metabolism Regulationmentioning
confidence: 99%